Môi trường nhà trường, tiền lương và sự thoả mãn công việc của giáo viên trung học phổ thông: Nghiên cứu trường hợp tại Thành phố Hồ Chí Minh - Phạm , Thị Hương; Đặng , Hùng Vũ (Tạp chí Giáo dục, 2021)
This study aims at investigating the effects of school climate and salary on job satisfaction of high school teachers. School climate scales by Rentoul and Frase (1983), Fisher and Frase (1991), Boyle, Borg, Falzon và Baglioni (1995) and Taylor and Tashakkori (1995) were adjusted and piloted for this study. The study surveyed 403 high school teachers in Ho Chi Minh City. The results show that several school climate factors positively affected teacher job satisfaction while work pressure and (low) salary negatively did. The article also suggests some recommendations for school governance to improve the school climate in Ho Chi Minh City.